2022
DOI: 10.3389/fncel.2022.917181
|View full text |Cite
|
Sign up to set email alerts
|

Targeting 17β-estradiol biosynthesis in neural stem cells improves stroke outcome

Abstract: Dax-1 (dosage-sensitive sex reversal adrenal hypoplasia congenital region on X-chromosome gene 1) blocks 17β-estradiol biosynthesis and its knockdown would be expected to increase 17β-estradiol production. We hypothesized that knockdown of Dax-1 in a conditionally immortalized neural stem cell (NSC) line, MHP36, is a useful approach to increase 17β-estradiol production. Short hairpin (sh) RNA targeted to Dax-1 in NSCs, namely MHP36-Dax1KD cells, resulted in the degradation of Dax-1 RNA and attenuation of Dax-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The function of estrogen, primarily 17β-estradiol , extends beyond its reproductive role to impact pathological processes, particularly in the CNS ( Rexrode et al, 2022 ; Zhang et al, 2023 ). Numerous studies highlight its protective role in brain injuries following ischemic stroke, involving the modulation of local and systemic immune responses post-stroke onset ( Petrone et al, 2014 ; Patkar et al, 2022 ). After a stroke, 17β-estradiol demonstrates neuroprotective effects by moderating inflammation, activating macrophages, and releasing anti-inflammatory cytokines (IL-10 and TGF-β) ( Akabori et al, 2010 ; Acosta-Martinez, 2020 ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…The function of estrogen, primarily 17β-estradiol , extends beyond its reproductive role to impact pathological processes, particularly in the CNS ( Rexrode et al, 2022 ; Zhang et al, 2023 ). Numerous studies highlight its protective role in brain injuries following ischemic stroke, involving the modulation of local and systemic immune responses post-stroke onset ( Petrone et al, 2014 ; Patkar et al, 2022 ). After a stroke, 17β-estradiol demonstrates neuroprotective effects by moderating inflammation, activating macrophages, and releasing anti-inflammatory cytokines (IL-10 and TGF-β) ( Akabori et al, 2010 ; Acosta-Martinez, 2020 ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…In fact, our data showed that aromatase is highly expressed in hippocampal SGZ of adult female mice (Figure 8C). Patkar et al also showed that aromatase is expressed in NSC and knockdown of Dax-1 can induce its overexpression [173]. As such, it is understandable that ubiquitous TPP2 depletion causes more severe impairment in learning and memory abilities than conditional TPP2 depletion, because all sources of estrogen may be damaged under ubiquitous TPP2 depletion.…”
Section: Figure 12mentioning
confidence: 99%
“…Accumulative evidence has demonstrated that estrogen, especially 17β-estradiol, has a protective role in brain injuries after ischemic stroke ( 16 ). This protective effect of 17β-estradiol is mediated by several mechanisms, including the regulation of local and systemic immune responses after stroke onset ( 17 ).…”
Section: Incidence and Severity Of Ischemic Stroke Based On Sexmentioning
confidence: 99%